DETERMINAN PERINGKAT OBLIGASI PADA PERUSAHAAN SEKTOR KEUANGAN - Siti Rahmah (2021)
This research is a quantitative research to determine the effect of leverage, activity ratio, and market value on bond ratings that was published by Indonesia Securities Rating Agency (PEFINDO) from the period of 2016 to 2019. Based on purposive sampling method, there were 25 financial companies. This research uses Microsoft Office Excel 2013 to analyze data and Panel Data Regression analysis by Eviews Program 11.1 with significant level 0.05 to test the hypothesis. Results from this research have shown that (1) Leverage proxied by debt to assets ratio (DAR) has no effect on bond ratings; (2) Activity ratio proxied by total assets turnover (TAT) has negative effects on bond ratings; (3) Market value proxied by market to book value (MBV) has negative effects on bond ratings. Keyword: Leverage; Activity Ratio; Market Value; Bond Ratings.